Parenting Fears and Concerns during Pregnancy: A Qualitative Survey - Alisa Wilska; Anja Rantanen; Elina Botha; Katja Joronen (MDPI AG, 2021)
Previous research on the fears and anxieties of expectant mothers has focused mostly on their fears about giving birth rather than parenting. This study aims to describe mothers' fears and concerns about parenthood during pregnancy and to examine the similarities and differences in the perspectives of primiparous and multiparous mothers. The qualitative research for this study was conducted in three postpartum units in Finland and focused on the responses to an open-ended question about parenting fears and concerns that was part of a questionnaire given to 250 mothers after they had given birth. The responses from the 128 mothers who answered this question were subject to inductive content analysis. Fears and concerns on parenthood included worries about coping with the future and everyday life with their new baby, the psychological burden of parenthood, their maternal resources and self-efficacy, meeting their baby's needs, their baby's health, concerns about their relationship with their partner and financial issues. Primiparous and multiparous mothers shared many of the same concerns, but some differences emerged. The findings contribute an interesting perspective to the social debate about declining birth rates and their psychosocial causes. Further studies are needed to examine the fears and concerns of younger adults, and even teens, about parenthood.